Lanreotide therapy in a case of thymic neuroendocrine carcinoma associated with syndrome of inappropriate antidiuretic hormone secretion - Gut, Paweł; Fischbach, Jakub; Baszko-Błaszyk, Daria; Fichna, Marta; Gryczyńska, Maria; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2011)
Neuroendocrine tumours of the thymus are rare neoplasms, which account for 2-4% of all anterior mediastinal tumours. Several endocrinopathies were found to be associated with these tumours, with ectopic ACTH secretion reported most frequently. Here we provide a description of the syndrome of inappropriate antidiuretic hormone secretion (SIADH) accompanying neuroendocrine thymic carcinoma. A mediastinal tumour was incidentally found on routine chest X-ray examination in a 55-year-old man. After detailed imaging studies, tumour excision was performed. The mediastinal tumour (11  8  4 cm) presented features of invasion to the left lung and pericardium. Histopathological examination confirmed the diagnosis of thymic neuroendocrine carcinoma. The patient was treated with chemotherapy because of the recurrence. Symptoms of carcinoid syndrome and positive result of the somatostatin receptor scintigraphy justified subsequent introduction of somatostatin analogue therapy. At this point low serum sodium levels accompanied by decreased serum osmolarity and inadequate urine concentration were found. Having excluded other typical causes, SIADH syndrome due to ectopic vasopressin synthesis was assumed. This finding adds to differential diagnosis of hyponatraemia, indicating that SIADH may also accompany thymic neuroendocrine tumours.